Venous gas embolism folowing hydrogen peroxide irrigation during debridement of chronic osteomyelitis lesion - Awang, Mohd Shukrimi; Che Ahmad, Aminudin; Mohd Amin, Azril; Mohamed, Abdul Hadi (Malaysian Medical Associations, 2006)
We report a case of a previous healthy 53 year old man who developed an intra-operative catastrophic event occuring in association with the use of hydrogen peroxide for wound irrigation following surgical debridement of a chronic osteomyelitis lesion of the humerus. it is our intention to highlight this potentially fatal consequence of hydrogen peroxide irrigation as part of bone debridement procedure. This case will serve as a reminder to orthopaedic surgeon who frequenctly use hydrogen peroxide in their surgical practice.